LEVEL ANALYSIS AND SUPPORTING FACTORS OF THINKING ABILITY ANALYTICAL IN SOLVING PROBLEM BASED PROBLEMS REVIEWED FROM THE LEARNING STYLES OF STUDENTS - Fitriani Fitriani; Wirawan Fadly (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
The ability to think analytically is one of the important abilities that must be mastered by students, being able to help students to analyze a problem logically, especially in looking for the relationship of concepts and situations that will be faced more easily, in addition to the ability to think analytically and logically play an important role to form patterns of logical structure in knowledge. The research method used is a mix-method that is a combination of methods (qualitative and quantitative) with a naturalistic design. This research was conducted at Ponorogo 1 Public Middle School with a sampling technique through purposive sampling. Data were collected through semi-structured interviews, observations and documentation which were then analyzed using quantitative descriptive and qualitative descriptive. This study investigated to determine the level of analytical thinking skills of students in solving problem-based problems in terms of learning styles and supporting factors in improving analytical thinking skills. The results showed that: 1) The level of analytical thinking ability in terms of the learning styles of students, namely (a) visual style students are at the level of ability to conclude the main ideas that are more dominant, (b) on audiovisual students that are at the ability to identify and knowing various errors, (c) in kinesthetic learning style students are at the level of ability to identify a problem and at this stage a good understanding is needed. (2) Factors supporting students' analytical thinking skills and learning styles, Through these results it is expected to provide theoretical and practical insights for educators in determining the approaches and strategies for achieving analytical science competencies according to the learning styles of students in schools.